2016
DOI: 10.1038/srep30999
|View full text |Cite
|
Sign up to set email alerts
|

Muscleblind-like 3 deficit results in a spectrum of age-associated pathologies observed in myotonic dystrophy

Abstract: Myotonic dystrophy type I (DM1) exhibits distinctive disease specific phenotypes and the accelerated onset of a spectrum of age-associated pathologies. In DM1, dominant effects of expanded CUG repeats result in part from the inactivation of the muscleblind-like (MBNL) proteins. To test the role of MBNL3, we deleted Mbnl3 exon 2 (Mbnl3ΔE2) in mice and examined the onset of age-associated diseases over 4 to 13 months of age. Accelerated onset of glucose intolerance with elevated insulin levels, cardiac systole d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
(116 reference statements)
3
12
1
Order By: Relevance
“…Since the presence of three MBNL paralogs was discovered ( 13 , 70 ), much attention has focused on determining the cellular functions and distinguishable features of these paralogs. In contrast to a previously described antagonistic effect of MBNL3 on MBNL1 activity ( 13 , 17 , 71 ), in the current study, we discovered a competitive interaction between MBNL paralogs and their isoforms that is determined by the organization of RNA regulatory elements and modulates AS profile (Figure 6 ). Initially, we observed that the loss of MBNL3 in myoblasts promotes the MBNL-mediated splicing profile (Figure 6 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Since the presence of three MBNL paralogs was discovered ( 13 , 70 ), much attention has focused on determining the cellular functions and distinguishable features of these paralogs. In contrast to a previously described antagonistic effect of MBNL3 on MBNL1 activity ( 13 , 17 , 71 ), in the current study, we discovered a competitive interaction between MBNL paralogs and their isoforms that is determined by the organization of RNA regulatory elements and modulates AS profile (Figure 6 ). Initially, we observed that the loss of MBNL3 in myoblasts promotes the MBNL-mediated splicing profile (Figure 6 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Initially, we observed that the loss of MBNL3 in myoblasts promotes the MBNL-mediated splicing profile (Figure 6 ). This splicing phenomenon was not evident either in adult heart or muscles of Mbnl3 KO mice, probably due to the relatively low contribution of MBNL3 to the total pool of MBNL in adult tissues ( 17 ). However, while MBNL3 predominates in cells lacking MBNL1 and MBNL2, the paralog shifts the AS profile towards MBNL-induced (Figure 6 and Supplementary Figure S11 ) what confirms a convergent splicing activity of MBNL paralogs and suggests their competitive interaction while present concomitantly in cells.…”
Section: Discussionmentioning
confidence: 99%
“…A logical consequence of this hypothesis is that loss-of-function mutations in G4C2-binding partners might contribute to ALS pathogenesis independently of and/or act synergistically with C9ORF72 expansions. Evidence in myotonic dystrophy supports this hypothesis: mutations in muscleblind-like proteins modify the phenotype caused by sequestration of the same proteins by CUG-repeat RNA (e.g., Choi et al, 2016 ). Similarly mice lacking muscleblind-like 1 exhibit some of the features of myotonic dystrophy despite the absence of CUG-repeat RNA (Dixon et al, 2015 ).…”
Section: Introductionmentioning
confidence: 97%
“…SMN1 (spinal motor neuron 1) is associated with the maintenance of the motor neurons [85]. MBNL3 belongs to a family of MBNL proteins that are affected in DM [86][87][88]. Misregulation of CUGBP1 in DM1 might affect these mRNAs (directly or indirectly); therefore, the number of genes, disrupted by CUGBP1 in DM1, might be great because each of these RNA-binding proteins controls own sets of mRNAs.…”
Section: Cugbp1 Is a Regulator Of Mrna Stabilitymentioning
confidence: 99%